Gaya Kepemimpinan Kepala Ruangan dengan Kepuasan Kerja (A Literatur Review) - Sigit Wahyudi; Abdul Rahman; Septinus Wonggor (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Job satisfaction is When an individual feels satisfied with his or her job, it manifests in a positive emotional disposition and passion for what they do. Work productivity is influenced by a nurse's job satisfaction which ultimately improves the standard of client care services. Management style is an important factor that affects employee satisfaction in the workplace. Leadership is the ability to manage an organization in such a way that individual and organizational goals are achieved. This study aims to determine the relationship between room manager management and nurse job satisfaction. The method used in this study is literature review. The main source of research data comes from an electronic database called Google Scholar for articles on hospital directors' leadership styles and nurses' performance satisfaction. Hasl data analysis showed that the relationship between room leadership style and job satisfaction of a nurse and the remaining 2 articles did not show a relationship between leadership style and job satisfaction of a nurse